OUTCOMES OF BELOW-THE-KNEE ENDOVASCULAR INTERVENTION FOR LIMB SALVAGE IN DIABETIC FOOT PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate limb salvage outcomes and identify factors associated with major amputation in diabetic foot patients undergoing below-the-knee endovascular revascularization.Subjects and methods: A single-center prospective observational study was conducted on 149 type 2 diabetic patients with foot ulcers and below-the-knee arterial lesions (occlusion or ≥70% stenosis) who underwent endovascular intervention at University Medical Center Ho Chi Minh City from January 2020 to December 2024. Outcome measures included limb salvage rate, primary patency, ulcer healing, hemodynamic improvement, complications, and factors associated with major amputation at 6 months.Results: The mean age was 67.5 ± 9.7 years, and 66.4% of patients were male. WIfI stage 3 accounted for 31.5% of cases. At 6 months, the limb salvage rate was 87.2%, primary patency was 84.6%, and ulcer healing was achieved in 73.2% of patients. The ankle–brachial index improved from 0.78 ± 0.21 to 0.95 ± 0.18 (p
Keywords: diabetic foot; below-the-knee endovascular intervention; limb salvage; peripheral artery disease; WIfI classification.